A New Test Method to Simulate Deep Drawing Phenomena on the Lab Scale. Issue 5 (25th August 2022) - Georgiou, E. P.; Drees, D.; Van der Donck, T.; Hazrati, J.; Veldhuis, M.; Aha, B.; Anderson, M.; Celis, J.-P.
Abstract: Expedient simulations and numerical modelling of forming processes depend on a good knowledge of the friction at the tool–sheet metal contact. The absolute value of the friction force or relative changes of this force due to changing conditions are vital input for a reliable numerical model. For that reason, a good selection of a laboratory experiment that can measure the friction under forming conditions is an essential step. This work is part of a large European Union project named ASPECT, which evaluates the friction force evolution in sheet metal forming as a result of changes in contact conditions. Simplified tribological lab-scale techniques showed an temperature dependence of friction opposite to what is measured in state-of-the-art macroscopic flat strip drawing tests. To understand and overcome this contradiction, a new method was developed to integrate the deformation aspect into a friction test; this approach assures closer resemblance to the actual forming conditions. The aim is to develop a method that measures the effect of temperature and speed on the resistance to sliding and deformation, and to provide an efficient prescreening and ranking of forming oils.